UMKM dalam Meningkatkan Perekonomian Indonesia - Ali Syafri (CV. Rumoh Aceh Publishing, 2025)
This article aims to find out government policies in improving the welfare of the community in the economic sector. This is done for micro, small and medium enterprises (MSMEs) are productive businesses owned by individuals or business entities with a relatively small number of employees, businesses, and turnover and are usually started with limited capital. Small and medium-sized businesses (MSMEs) have a significant role in the national economy, both in absorbing labor, contributing foreign exchange, and contributing to GDP. MSMEs are divided into three categories based on revenue: Micro Enterprises with business profits of 300 million, Small Enterprises with business profits above 300 million, and Medium Enterprises with business profits of more than 2.5 billion. The research method used in writing this article is the literature review method from various journal sources related to the role of MSMEs in improving the Indonesian economy.